[OP.2A.01] URINE CADMIUM LEVELS AND ALBUMINURIA IN A GENERAL POPULATION FROM SPAIN: A GENE-ENVIRONMENT INTERACTION POPULATION-BASED STUDY. (September 2016) - Pichler, G.; Grau-perez, M.; Martin-escudero, J.; Galan-chilet, I.; Dominguez-lucas, A.; Chaves, F.; Redon, J.; Tellez-plaza, M.
Abstract : Objective: Chronic exposure to low levels of cadmium is an increasingly recognized concern, as cadmium biomarkers at relatively low concentrations have been associated with a number of health conditions including cancer and bone, kidney and cardiovascular disease. The aim of the present study was to evaluate the cross-sectional association between urine cadmium and albuminuria in a representative sample of the general population from Valladolid (Spain), and to test the hypothesis that specific genotypes in candidate genes related to oxidative stress may confer increased susceptibility to cadmium. Figure. No caption available. Design and method: Cadmium exposure was estimated by inductively coupled plasma mass spectrometry (ICPMS). Urine albumin was measured by automated nephelometric immunochemistry. 396 single nucleotide polymorphisms (SNPs) from 92 oxidative stress and albuminuria-related candidate genes were genotyped by SNPlex. Results: 1397 participants (mean age 49.7 ± 0.2, 49% males, 35.9% hypertensives, 5.6% diabetics, 44.6% never smokers) were included. The prevalence of albuminuria (albumin-creatinine ratio greater than or equal to 30 mg/g in women and greater than or equal to 20 mg/g in men) was 30%. The median levels of urine cadmium was 0.39 (IQR, 0.23–0.65) microgram per gram of creatinine. Multivariable-adjusted geometric mean ratios of albuminuria comparing the two highest to lowest tertiles of urine cadmium were 1.63 (95% CI, 1.43–1.85) and 2.92 (95% CI, 2.56–3.33), respectively (P for trend <0.001). The association between urine cadmium and albuminuria was observed across all participant subgroups evaluated and was evident for both micro- and macroalbuminuria (figure 1). At the Bonferroni-corrected level, significant differential associations of urine cadmium levels and albuminuria by genotipes of rs4720672 polymorphism in RAC1 gene were observed. Conclusions: Increasing urine cadmium concentrations were cross-sectionally associated with increased albuminuria in a representative sample of a general population from Spain. Certain genotypes may confer differential susceptibility to potential cadmium effects.